2018
DOI: 10.3389/fmicb.2018.02362
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparison of Techniques for Collecting Skin Microbiome Samples: Swabbing Versus Tape-Stripping

Abstract: The swabbing and tape-stripping methods have traditionally been used for collecting skin microbiome samples for skin bacterial analysis, although no reports have compared the outcome of these methods for collecting skin bacteria. Our purpose was to show the differences in microbial composition between samples collected using the swabbing and tape-stripping methods, by both the next generation sequencing and culture studies. The skin microbiome was collected by both methods, and the samples were processed for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 45 publications
(57 reference statements)
1
85
2
4
Order By: Relevance
“…reported minimal differences when comparing results from skin swabs, scrapings and biopsies. Concordance between swabbing and tape stripping has also been confirmed in several studies …”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…reported minimal differences when comparing results from skin swabs, scrapings and biopsies. Concordance between swabbing and tape stripping has also been confirmed in several studies …”
Section: Discussionsupporting
confidence: 56%
“…However, the changes in the microbiome during treatment were not detected by the culture data. In fact, it has recently been reported that the tape stripping method may capture more viable bacteria than swabbing . It could be speculated that changes in bacterial populations may have been too subtle to be detected by culture or that changes are predominantly in nonculturable species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the swabbing technique, the tape‐stripping method allows to ‘peel off’ bacteria from the stratum corneum as well as deeper layers. A recent study by Ogai and coworkers showed that next generation sequencing analysis of microbial samples collected with the tape‐stripping method revealed a slightly higher abundance of Cutibacterium spp., which are known anaerobic bacteria, compared to the ones collected using the swabbing method. This might suggest that the tape‐stripping technique allows for a deeper sampling of the stratum corneum reaching the anaerobic portions of the skin appendages.…”
Section: Currently Available Sampling Methods To Analyse the Skin Micmentioning
confidence: 99%